2019
DOI: 10.3390/gidisord1020023
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Colon Carcinogenesis: Expectation for Inhibition of Colon Carcinogenesis by Oral Hypoglycemic Drugs

Abstract: The global deaths due to colorectal cancer and diabetes mellitus have increased by 57% and 90%, respectively. The relationship between various cancers and diabetes mellitus has been shown in multiple epidemiological studies. Hence, better management of diabetes mellitus is expected to reduce the risk of various cancers. This review focuses on colorectal cancer and aims to summarize recent findings on the antitumor effects of various oral hypoglycemic drugs on colorectal cancer and their estimated mechanisms. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 135 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…34 This might enhance IGF and Wnt signaling systems and result in CRC carcinogenesis. 36 Zhao et al 37 reported that some dietary fibers manipulated the gut microbiota and enhanced the production of shortchain fatty acids. Overgrowing bacteria which produce these fatty acids directly associated with the reduction in the level of glycated hemoglobin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 This might enhance IGF and Wnt signaling systems and result in CRC carcinogenesis. 36 Zhao et al 37 reported that some dietary fibers manipulated the gut microbiota and enhanced the production of shortchain fatty acids. Overgrowing bacteria which produce these fatty acids directly associated with the reduction in the level of glycated hemoglobin.…”
Section: Resultsmentioning
confidence: 99%
“…When the level of lipopolysaccharides increases in the blood, insulin resistance organs such as skeletal muscle and liver become insulin resistant which finally leads to hyperinsulinemia 35 . This might enhance IGF and Wnt signaling systems and result in CRC carcinogenesis 36 . Zhao et al 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of TNF‐α in skeletal muscle atrophy has been extensively investigated 27–32 . One study demonstrated that TNF‐α produced in fibrotic liver was transported to muscle through the bloodstream, leading to atrophy of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TNF-α in skeletal muscle atrophy has been extensively investigated. [27][28][29][30][31][32] One study demonstrated that TNFα produced in fibrotic liver was transported to muscle through the bloodstream, leading to atrophy of skeletal muscle. They also conducted an in vitro study using a muscle cell line and serum from mice with liver fibrosis, indicating an exclusive impact of serum TNF-α on myotube atrophy.…”
Section: Discussionmentioning
confidence: 99%